Marine pollution and the South Asian Coastal States: A legal appraisal - Karim, M.E. (Macquaire University, 2013)
South Asia is the living place of more than one-fifth of the world’s population and it is the most densely populated region in the world. There are five coastal states in this region (i.e. Bangladesh, India, Maldives, Pakistan and Sri Lanka) and due to their great reliance on the sea for their livelihood, the people here contribute toward pollution which may have disastrous consequences in the long run. This article, with a brief focus on international and regional legal initiatives on marine pollution, considers the existing municipal legal framework to handle the issue in these countries. It has been revealed that this issue of marine pollution is not considered seriously yet and the existing laws are mostly outdated and leniently implemented.